(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless sensor network have recently come into prominence because they hold the potential to revolutionize segment of our economy and life with its wide applications. Unlike a centralized system, a sensor network is formed by large numbers of networked sensing nodes. They are having unique set of resource constraints such as finite onboard battery power and limited network communication bandwidth. Since running real experiments is costly and time consuming, simulation is essential to study Wireless Sensor Networks (WSN). It is rather complex, or even unfeasible, to model analytically a WSN and it usually leads to oversimplified analysis with limited confidence. Therefore, simulation is essential to study WSN. The word “wise” in the title indicate the meaning most appropriate according to their usage and testing